Let $X$ be a real vector space. Let $\varphi_1,\dots, \varphi_n $ and $\psi$ be linear maps from $X$ to $\mathbb{R}$. The following are equivalent:

  1. There exist $\lambda_1, \dots, \lambda_n \in \mathbb{R}$ such that $\psi = \sum_{i=1}^n \lambda_i \varphi_i$.

  2. $\bigcap_{i=1}^n \ker{\varphi_i} \subset \ker{\psi}$.

It is clear that 1) implies 2). But not at all that 2) implies 1) (at least to me). Here is what I tried:

The statement is easy if $n=1$: Indeed if $\varphi_1 = 0$, set $\lambda_1 = 0$, and otherwise pick $x_1 \notin \ker \varphi_1$ and set $\lambda_1 = \psi(x_1)/\varphi(x_1)$. Because then, since an arbritrary $x \in X$ can be written as $x = \alpha_1 x_1 + v$ with $\alpha_1 \in \mathbb{R}$ and $v \in \ker \varphi_1$, we get $$\lambda_1 \varphi_1(x) = \frac{\psi(x_1)}{\varphi(x_1)} \varphi_1(\alpha_1 x_1 + v) = \psi(\alpha_1 x_1) = \psi(\alpha_1 x_1 + v) = \psi(x).$$

Now let $n\geq 2$ and suppose the implication $2) \rightarrow 1)$ holds for $n-1$. If, for some index $i \in \lbrace 1, \dots ,n \rbrace$, the set $S_i:=\bigcap_{j\neq i} \ker\varphi_j \setminus \ker \varphi_i$ was empty, then $\bigcap_{j=1}^n \ker \varphi_j = \bigcap_{j\neq i} \ker\varphi_j$ and by induction we could express $\psi$ as a linear combination of the $\varphi_j$'s with $j\neq i$. Thus, suppose $S_i \neq \emptyset$ for all $i$ and pick $x_i \in S_i$. Now by plugging the $x_i's$ into the equation for $\psi$ we're after, we find $\lambda_i = \psi(x_i)/\varphi_i(x_i)$. So it should be possible to prove that we have $\psi = \sum_{i=1}^n {\frac{\psi(x_i)}{\varphi_i(x_i)}}\varphi_i$, right?

But how? I couldn't do it. Is there a mistake in my reasonning? I used the direct sum decompositions $X = \mathbb{R}x_i \oplus \ker\varphi_i$ to write an arbitrary $x \in X$ in $n$ different ways and to get rid of the denomintors $\varphi_i(x_i)$ but then I am left with $\psi(\alpha_1 x_1 + \dots + \alpha_n x_n)$ which should equal $\psi(x)$.


This is fine. Write $x\in X$ as $\sum a_ix_i+x'$ with $\varphi_i(x')=0$ for every $i$. Then $\psi(x)=\sum a_i\psi(x_i)$ and $(\sum \psi(x_i)/\varphi_i(x_i)\varphi_i)(x)=\sum a_i \psi(x_i)/\varphi_i(x_i)\varphi_i(x_i)=\sum a_i\psi(x_i)$, as desired.

  • $\begingroup$ Thank you very much, Kevin! Just to make sure I understand how the a_i's and x' are chosen; First we write x = a_1 x_1 + v_1 with v_1 in the kernel of the first map, then we write v_1 as a_2 x_2 + v_2 with v_2 in the kernel of the second map, and so on, right? $\endgroup$
    – m.s
    Oct 29 '15 at 21:13
  • $\begingroup$ Yeah, sure! Or just use that the $x_i$ are linearly independent since they're all in the kernels of different sets of functionals, so you could choose a basis including them. $\endgroup$ Oct 29 '15 at 22:28

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.